Left ventricular orientation and position in an advanced heart failure population - Antonia E. Curtin; Kevin V. Burns; Ryan M. Gage; Alan J. Bank (Elsevier, 2017)
Introduction: Previous canine and in silico studies indicate that left ventricular (LV) orientation and position have clinically significant effects on standard ECG elements, which are particularly relevant in an advanced heart failure (HF) population. Our objectives were to investigate the real-world implications of these previous results by describing for the first time the range of LV orientations and positions in HF patients, identifying clinical predictors of orientation and position, and investigating how thoracic geometry may affect orientation and position. Materials and methods: Cardiac MRIs were used to measure LV orientation angles, LV position, chest dimensions, and the ratio of LV volume to thoracic area (LVTR). Multivariate regression analyses were used to identify significant predictors of orientation and position. Results: The mean frontal plane LV orientation angle was 31 ± 11° (range, 0°-47°) and fell within the ranges used in previous studies of orientation effects. Orientation in the transverse plane, the effects of which have not been simulated, averaged 48 ± 10° (range, 21°-71°). The ranges of LV positions in the frontal and transverse planes (7.9 and 5.6 cm, respectively) are similar to or greater than those used in silico. Orientation and position were weakly correlated with multiple significant predictors, and the relationship between HF progression and LV orientation and position could not be determined. Conclusion: Variation in LV orientation and position in advanced HF patients is large and cannot be readily predicted using the standard clinical variables or additional thoracic geometry measures used in this study. These findings may have significant clinical implications because of the possible effects of orientation and position on key ECG features. New tools and additional studies are needed before LV orientation or position data can be incorporated into clinical ECG interpretation. Keywords: Heart orientation, Heart position, Systolic heart failure, MRI